Human trafficking - Segrave, Marie, 1979- (Farnham, Surrey, England : Ashgate Publishing Limited, 2013)
Human trafficking captured the attention of the global community well over a decade ago, inspiring multifarious international, national, regional and local responses. While formally recognized as one of the major threats associated with transnational organized crime, human trafficking remains an issue about which much has been written and yet little is known or supported by empirical evidence. The essays selected for this volume reflect four key areas of debate: the transnational organized crime framework; the data and research landscape; the implementation of anti-trafficking responses; and the articulation of alternative responses to human trafficking. These essays are written by well-known and more recent contributors to this field of research. The collection draws attention to contemporary arguments as well as recent empirical research, and points to the importance of contextualizing human trafficking within both the global and local setting. This volume reflects where human trafficking data, research and debate is currently located and where it is heading, and as such is of interest to academics, students, policymakers and practitioners.
Part I. ANALYSING THE FRAMEWORK: 1.'(Un)Popular Strangers and Crises (Un)Bounded: Discourses of Sex-Trafficking, the European Political Community and the Panicked State of the Modern State', European Journal of International Relations, 9, pp. 37-86 / Jacqueline Berman; 2. 'The Perverse Politics of Four-Letter Words: Risk and Pity in the Securitisation of Human Trafficking', Millennium: Journal of International Studies, 33, pp. 251-77 / Claudia Aradau; 3. 'Child Trafficking or Teenage Migration? Bolivian Migrants in Argentina', International Migration, 43, pp. 57-89 / Tanja Bastia; 4. 'Trafficking and Transnational Organised Crime', in Trafficking and Global Crime Control, London: Sage, pp. 83-105 / Maggy Lee -- part II. DATA ON HUMAN TRAFFICKING: WHAT WE KNOW, HOW WE KNOW IT AND IMPLICATIONS: 5. 'The Illusiveness of Counting'Victims' and the Concreteness of Ranking Countries: Trafficking in Persons from Colombia to Japan', in P. Andreas and K.M. Greenhill (eds), Sex, Drugs and Body Counts, Ithaca: Cornell University Press, pp. 110-26 / Kay B. Warren; 6. 'Data on Human Trafficking: Challenges and Policy Context', in John Winterdyck, Benjamin Perrin and Philip Reichel (eds), Human Trafficking: Exploring the International Nature, Concerns and Complexities, Boca Raton: CRC Press, pp. 39-56 / Jo Goodey; 7. 'Images and Evidence: Human Trafficking, Auditing, and the Production of Illicit Markets in Southeast Asia and Beyond', Public Culture, 22, pp. 223-36 / Johan Lindquist; 8. 'Representing Trafficking: Media in the United States, Great Britain, and Canada', in Alison Brysk and Austin Choi-Fitzpatrick (eds), From Human Trafficking to Human Rights: Reframing Contemporary Slavery, Pennsylvania: University of Pennsylvania Press, pp. 44-69 / Girish J. Jeff' Gulati; 9. 'Comparative Models of Reporting Mechanisms on the Status of Trafficking in Human Beings', Vanderbilt Journal of Transnational Law, 41, pp. 1355-415 / Mohamed Y. Mattar -- part III. IMPLEMENTING COUNTER-TRAFFICKING STRATEGIES: 10. 'Human Trafficking, Information Campaigns, and Strategies of Migration Control', American Behavioral Scientist, 50, pp. 1674-95 / Cine Nieuwenhuys and Antoine Pecoud; 11. 'Where Are All the Victims? Understanding the Determinants of Official Identification of Human Trafficking Incidents', Criminology and Public Policy, 9, pp. 201-33 / Amy Farrell, Jack McDevitt and Stephanie Fahy; 12. 'Human Trafficking and Legal Culture', Israel Law Review, 43, pp. 479-513 / David Nelken; 13. 'Repatriation: Returning Women Home', Sex Trafficking: International Context and Response, Cullompton: Willan pp. 160-92 / Marie Segrave, Sanja Milivojevic and Sharon Pickering -- partt IV ALTERNATIVE FRAMEWORKS: 14. 'Beyond a Snapshot: Preventing Human Trafficking in the Global Economy', Indiana Journal of Global Legal Studies, 13, pp. 137-63 / Janie Chuang; 15. 'The Human Rights Quagmire of'Human Trafficking'', Virginia Journal of International Law, 49, pp. 1-59 / James C. Hathaway; 16. Human Rights and Human Trafficking: Quagmire or Firm Ground? A Response to James Hathaway', Virginia Journal of International Law, 49, pp. 789-848 / Anne T. Gallagher.
Includes bibliographical references and index.
Keywords: Human trafficking -- Law and legislation; Human trafficking -- Prevention